Are antigen tests useful as screening for the identification of SARS-CoV-2 in emergency rooms?. (20th October 2021) - Cigliano, F; Boccuzzi, A; Basile, V; Ferraro, A; Macciotta, A; Catalano, A; Costa, G; Vineis, P; Sacerdote, C; Caramello, V
Abstract: Background: A quick and accurate case identification in the Emergency Department (ED) during the SARS-CoV-2 pandemic is crucial for clinical management and to prevent spread of infections. The gold standard for diagnosing SARS-CoV-2 infection is the real-time reverse transcription polymerase chain reaction (RT-PCR) test in upper airways swabs. However, the procedure is available in few specialized laboratories and requires an average sample processing time of about 6 hours from its inception. The development of reliable but cheaper and faster point-of-care tests was expected to be useful either for population-screening or as first aid tests in the ED. Rapid antigenic diagnostic tests (Ag-RDTs), directly detect SARS-CoV-2 proteins produced by the replicating virus in respiratory specimens, were proved to be candidates in both cases. However, data on their effectiveness are still few and controversial. The aim of the study is to establish the accuracy of antigen tests to identify SARS-CoV-2 in a high prevalence setting. Methods: Results of 324 patients, consecutively admitted to the ED of San Luigi Gonzaga University Hospital in Orbassano (Turin, Italy) between 26 October and 10 November 2020 and subjected to both molecular and antigen tests, were compared. Results: Using RT-PCR as gold standard, specificity and sensitivity of Ag-RDT were 0.94 (95%CI: 0.90-0.98) and 0.80 (95%CI: 0.75-0.85), respectively. The Ag-RDT positive predictive value was 0.96 (95%CI 0.93- 0.99), and the negative predictive value was 0.72 (95% CI: 0.65-0.79). Patients that tested negative to Ag-RDT but presented with fever and cough or had pneumonia at imaging were more likely to be false negatives. Ag-RDTs best performance occurs in the first days after symptom onset. Conclusions: These results confirm the limits of antigenic tests as first line screening tests and suggest that the antigenic test should be integrated with clinical judgement, based on physical and instrumental examinations. Key messages: Antigenic tests have a limited effectiveness as first line screening tests. In a high-prevalence setting these tests incorrectly judge as negative many COVID-19 symptomatic patients, making necessary to integrate their results with clinical judgement.